Drilling dimension effects in early stages of osseointegration and implant stability in a canine model - Baires-Campos, Felipe-Eduardo (Med Oral Patol Oral Cir Bucal, 2015)
BACKGROUND: This study histologically evaluated two implant designs: a classic thread design versus another specifically designed for healing chamber formation placed with two drilling protocols. MATERIAL AND METHODS: Forty dental implants (4.1 mm diameter) with two different macrogeometries were inserted in the tibia of 10 Beagle dogs, and maximum insertion torque was recorded. Drilling techniques were: until 3.75 mm (regular-group); and until 4.0 mm diameter (overdrilling-group) for both implant designs. At 2 and 4 weeks, samples were retrieved and processed for histomorphometric analysis. For torque and BIC (bone-to-implant contact) and BAFO (bone area fraction occupied), a general-linear model was employed including instrumentation technique and time in vivo as independent. RESULTS: The insertion torque recorded for each implant design and drilling group significantly decreased as a function of increasing drilling diameter for both implant designs (p<0.001). No significant differences were detected between implant designs for each drilling technique (p>0.18). A significant increase in BIC was observed from 2 to 4 weeks for both implants placed with the overdrilling technique (p<0.03) only, but not for those placed in the 3.75 mm drilling sites (p>0.32). CONCLUSIONS: Despite the differences between implant designs and drilling technique an intramembranous-like healing mode with newly formed woven bone prevailed. Key words: Histomorphometry, biomechanical, in vivo, initial stability, insertion torque, osseointegration.